Iodine-Promoted N-Acylation of Amines with Hydrazide: An Efficient Metal-Free Amidation - Tian, Long; Zhang, Qianwei; Ablajan, Keyume (Synthesis, 2022)
An efficient protocol for the amidation of hydrazide with amine has been developed by utilizing I2 as an oxidant under metal- and base-free conditions at room temperature. N-Acylation products of amines were obtained in good to excellent yields without using toxic reagents. This method is operationally straightforward and tolerates aliphatic/aromatic and primary/secondary amines with different hydrazides.
Keywords: amidation; metal-free; hydrazide; oxidant; acylation